Algorithms and architectures for low-cost license plate recognition system - Ku, Wei Chiet (2012)
License plate recognition system has its application in many areas such as recording parking statistics, identifying car thefts and monitoring traffic flow. Though several effective solutions have been proposed, the computation complexity has been one of the main limitations. Commercial mobile license plate recognition systems continue to suffer from the shortcomings of high cost and bulky implementation. This thesis presents several novel algorithms in an attempt to realize a low-cost license plate recognition system capable of real-time performance.